Sensitivitas Usahatani Pisang Kepok di Desa Bangun Harja di Kecamatan Seruyan Hilir Timur Kabupaten Seruyan - Lili Winarti (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
This study aimed to analyze the sensitivity of the bananas kepok farm in the village Bangun Harja District of Seruyan Hilir Timur Regency Seruyan. The method used is in sampling with simple random method (Simple Random Sampling), using the method slovin with a confidence level of 10%, obtained samples of 74 banana growers, for represent the entire population of banana growers in the village Bangun Harja Kecamtan Seruyan Hilir Timur Regency Seruyan. Analysis of the data used is the analysis of qualitative and quantitative analysis, qualitative analysis performed to obtain a picture or descriptive farming bananas kepok and quantitative analysis was conducted to analyze the costs incurred for activities ranging from the cost of investment, operational, production to marketing and financial analysis used to knowing feasible or not his farming bananas kepok using the criteria for eligibility of investment are: Net Present Value (NPV), Internal rate of Return (IRR), Net Benefit Cost ratio (Net B / C), Payback Period and then performed a sensitivity analysis to determine the level of sensitivity to the changes in the farm scenario 1 and 2 were used. The results of the sensitivity analysis shows that the decline in selling prices of bananas kepok more sensitive than the increase in operating costs of farming bananas kepok and a decrease in selling prices of bananas kepok 20%, would lead to farm bananas kepok not worth the effort views of NPV, IRR, Net B/C and Payback Period.